Thromboplastin Related Differences in the Determination of International Normalised Ratio: A Cause for Concern? - Kitchen, S; Walker, I D; Woods, T A L; Preston, F E (Thrombosis and Haemostasis, 1994)
When the International Normalised Ratio (INR) is used for control of oral anticoagulant therapy the same result should be obtained irrespective of the laboratory reagent used. However, in the UK National External Quality Assessment Scheme (NEQAS) for Blood Coagulation INRs determined using different reagents have been significantly different.For 18 NEQAS samples Manchester Reagent (MR) was associated with significantly lower INRs than those obtained using Diagen Activated (DA, p = 0.0004) or Instrumentation Laboratory PT-Fib HS (IL, p = 0.0001). Mean INRs for this group were 3.15, 3.61, and 3.65 for MR, DA, and IL respectively. For 61 fresh samples from warfarin-ised patients with INRs of greater than 3.0 the relationship between thromboplastins in respect of INR was similar to that observed for NEQAS data. Thus INRs obtained with MR were significantly lower than with DA or IL (p <0.0001). Mean INRs for this group were 4.01, 4.40, and 4.59 for MR, DA, and IL respectively.We conclude that the differences between INRs measured with the thromboplastins studied here are sufficiently great to influence patient management through warfarin dosage schedules, particularly in the upper therapeutic range of INR. There is clearly a need to address the issues responsible for the observed discrepancies.